Crystal methamphetamine use in British Columbia, Canada: A cross-sectional study of people who access harm reduction services. - Kristi Papamihali (Public Library of Science (PLoS), 2021)
Introduction Increased use of crystal methamphetamine ("crystal meth") has been observed across North America and international jurisdictions, including a notable increase in the presence of methamphetamines in illicit drug toxicity deaths in British Columbia (BC), Canada. We used data from a cross-sectional survey and urine toxicology screening to report the prevalence, correlates, and validity of self-reported crystal meth use among clients of harm reduction sites in BC. Materials and methods Survey data were collected from 1,107 participants across 25 communities in BC, through the 2018 and 2019 Harm Reduction Client Survey. We described reported substance use and used a multivariate logistic regression model to characterize crystal meth use. Urine samples provided by a subset of participants were used to derive validity of self-reported three-day crystal meth use compared to urine toxicology screening. Results Excluding tobacco, crystal meth was the most frequently reported substance used in the past three days in 2018 and 2019 (59.7% and 71.7%, respectively). Smoking was the dominant route of administration for crystal meth, crack, heroin, and fentanyl. Multivariate analysis determined significantly higher odds of crystal meth use among those who used opioids (Adjusted Odds Ratio [AOR] = 3.13), cannabis (AOR = 2.10), and alcohol (1.41), and among those who were not regularly housed (AOR = 2.08) and unemployed (AOR = 1.75). Age ≥50 was inversely associated with crystal meth use (AOR = 0.63). Sensitivity of self-reported crystal meth use was 86%, specificity was 86%, positive predictive value was 96%, and negative predictive value was 65%. Conclusions Crystal meth was the most commonly used substance among clients of harm reduction sites in BC in 2018 and 2019, and was frequently used concurrently with opioids. Comparison to urine samples demonstrated high validity of self-reported crystal meth use. Understanding evolving patterns of substance use will be imperative in tailoring harm reduction and substance use services for individuals that use crystal meth.